The Indian constituent assembly and the making of Hindus and Muslims in Jammu and Kashmir - Rai, Mridu (Asian affairs, 2018)
Article 370 of the Indian constitution gives the northern province of Jammu and Kashmir special status within the union. Today that provision forms a nucleus of fierce political contention between secularists and religious nationalists in India, despite the manifest whittling down of the article's most significant aspects. This development is counterintuitive: the original intent of the article's introduction had no relation to questions of religion. This essay attempts to understand this unanticipated role, as a marker of the state's secularity or lack thereof, the article has come to play in Indian politics. It contends that the seeds were sown even at the time of shaping the Indian constitution of a perspective that viewed the people of Jammu and Kashmir according to their religious affiliations. (Asian Aff/GIGA)